Taming globalisation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Development and the information age. IDRC. 1998. 65 pp. ISBN 0 88936 851 1 Free from IDRC PO Box 8500 Ottawa, ON, Canada KIG 3H9.